Fiscal Decentralization, Chinese Style: Good for Health Outcomes? - Johannes P. Jütting; Hiroko Uchimura (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
This study analyzes the effect of fiscal decentralization on health outcomes in China using a panel data set with nationwide county-level data. We find that counties in more fiscal decentralized provinces have lower infant mortality rates compared with those counties in which the provincial government retains the main spending authority, if certain conditions are met. Spending responsibilities at the local level need to be matched with county government?s own fiscal capacity. For those local governments that have only limited revenues, their ability to spend on local public goods such as health care depends crucially upon intergovernmental transfers. The findings of this study thereby support the common assertion that fiscal decentralization can indeed lead to more efficient production of local public goods, but also highlights the necessary conditions to make this happen.
Keywords: 330